2013
DOI: 10.1021/ar400012w
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Thioester Equivalents for Protein Chemical Synthesis

Abstract: The chemical synthesis of proteins provides synthetic chemists with an interesting challenge and supports biological research through the generation of proteins that are not produced naturally. Although it offers advantages, studies of solid phase peptide synthesis have established limits for this technique: researchers can only prepare peptides up to 50 amino acids in length in sufficient yields and purity. Therefore, researchers have developed techniques to condense peptide segments to build longer polypepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(91 citation statements)
references
References 68 publications
0
90
0
1
Order By: Relevance
“…One important step toward the design of mild transamidation and amide metathesis reactions that operate with peptide substrates in water was inspired by recent advances in the design of N,S-acyl shift systems ( Figure 3) [13][14][15][16][17][18][19][20]21 ]. Indeed, some N-(2-sulfanylethyl) amides are able to rearrange into transient thioesters by spontaneous acyl migration from nitrogen to sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…One important step toward the design of mild transamidation and amide metathesis reactions that operate with peptide substrates in water was inspired by recent advances in the design of N,S-acyl shift systems ( Figure 3) [13][14][15][16][17][18][19][20]21 ]. Indeed, some N-(2-sulfanylethyl) amides are able to rearrange into transient thioesters by spontaneous acyl migration from nitrogen to sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…These methods were problematic for several reasons, including the favorable Curtius rearrangement which acyl azides readily undergo. In an attempt to overcome these limitations, Liu and co-workers have investigated extensively peptide hydrazines and their conversion to acyl azides [134]. They found that the conversion of hydrazide 96 to acyl azide 97 could be completed nearly C. Subsequent addition of thiols, such as MPAA, to the reaction mixture, followed by an increase in pH to 7.0, reliably generated the required thioester 98 in a convenient one-pot procedure.…”
Section: New Methods For Activated Peptide Synthesismentioning
confidence: 99%
“…The two peptide fragments may be obtained by solid-phase peptide synthesis using well-established fluorenylmethoxycarbonyl (Fmoc-) or tertbutyloxycarbonyl (Boc-) amine protecting group strategies. Several chemical linkers and derivatization strategies are available for the synthesis of peptide α-thioesters by both chemistries [49,50]. Since most histone marks are found in the N-terminal tails, the C-terminal fragment may be larger and obtained by heterologous expression in Escherichia coli (Figure 8.2).…”
Section: Strategies Of Native Chemical and Expressed Protein Ligationmentioning
confidence: 99%